2015
DOI: 10.1016/j.biotri.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of polymer wear debris from total disc arthroplasty

Abstract: a b s t r a c tTotal disc arthroplasty is an alternative to spinal fusion, aimed at preserving flexibility; these devices typically involve a cobalt chrome molybdenum alloy socket articulating against an ultra-high molecular weight polyethylene (UHMWPE) ball. As with all artificial joints, wear debris is of particular concern due to its effect on both implant life and the in vivo biological reactions that can occur. In this paper, a profile of the UHMWPE wear debris generated from disc arthroplasty, tested on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Surface roughness can be quantified using Ra (the arithmetic average of absolute values of sampling length). Although its applications are mainly in tribology and wear, 21 , 60 it has recently been used to study biological tissues such as articular cartilage in order to assess its surface roughness. 35 , 88 It has also been trialled for cardiovascular applications, not involving tribology.…”
Section: Introductionmentioning
confidence: 99%
“…Surface roughness can be quantified using Ra (the arithmetic average of absolute values of sampling length). Although its applications are mainly in tribology and wear, 21 , 60 it has recently been used to study biological tissues such as articular cartilage in order to assess its surface roughness. 35 , 88 It has also been trialled for cardiovascular applications, not involving tribology.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the subsphaeroidal wear debris from the artificial hip joints took up the majority of the debris but shared a smaller percentage of the total volume, indicating the type distribution was imbalanced [12]. Eckold et al [23] suggested that the majority of the morphological occurrences of wear particles from artificial discs was fibril. Regarding the artificial knee and hip joints, it was concluded that the particle morphology can be strongly influenced by the lack of experimental precision with different quantitative approaches and the in vivo wear particle distribution was not homogeneous owing to the clumping and clearing of particles through drainage [10].…”
Section: Introductionmentioning
confidence: 99%
“…The physical properties of the surfaces of the materials are usually quantified through their mean surface roughness, Ra, the arithmetic average of absolute values of sampling length [17]. Applications are typically associated with tribology and wear [18, 19], which has led to the biomedical studies of articulating tissues such as the articular cartilage [20, 21]. Recently, though, the feasibility of quantitatively measuring the surface roughness has been established for the coronary arteries [1, 22], which provides a step change from qualitative surface analysis [23].…”
Section: Introductionmentioning
confidence: 99%